The Hidden Prices of Inflation (Observatorio Económico, 2008)
After more than a decade of relatively stable prices, a rise in the cost of goods and services has brought back to mind the forgotten—though not banished—image of inflation out of control. What has happened, and what could happen, to households' spending capacity and to their access to goods and services? Continue reading...
Keywords: Inflation; Spending capacity; Goods and services